2009
DOI: 10.1007/s11665-009-9539-y
|View full text |Cite
|
Sign up to set email alerts
|

Dissolution of Eutectic β-Mg17Al12 Phase in Magnesium AZ91 Cast Alloy at Temperatures Close to Eutectic Temperature

Abstract: Knowledge on the dissolution kinetics of b -eut phase in cast Mg AZ91 alloy at temperatures close to the eutectic temperature is very useful for various processes of the alloy. In the present study, dissolution of b -eut phase has been investigated experimentally and considered theoretically. Results have confirmed that the kinetics of b -eut dissolution is basically diffusion controlled. Optimum times for dissolution heat treatment practice of different sizes of cast microstructure which are cooling rate depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 24 publications
0
11
0
Order By: Relevance
“…The lamellae structure (position 3) involves the lamellar growth of Mg 17 Al 12 into the α-Mg grains, corresponding to the discontinuous precipitation [12] . Zhu et al [16] also found the similar β-lamellae structure that mostly appeared to grow near the eutectic Mg 17 Al 12 . This is because these regions have relatively higher Al contents.…”
Section: As-cast Microstructurementioning
confidence: 71%
“…The lamellae structure (position 3) involves the lamellar growth of Mg 17 Al 12 into the α-Mg grains, corresponding to the discontinuous precipitation [12] . Zhu et al [16] also found the similar β-lamellae structure that mostly appeared to grow near the eutectic Mg 17 Al 12 . This is because these regions have relatively higher Al contents.…”
Section: As-cast Microstructurementioning
confidence: 71%
“…Turen [9] investigated that, 0.5 wt.% Sn addition to AZ91 alloy, transformed the lamellar eutectic structure into fully divorced β eutectic, forming fine Mg 2 Sn phase that distributed throughout α-Mg matrix, which could block the movement of dislocation by Orowan looping. Li et al [10] also reported that Sn addition could suppress the formation of discontinuous precipitation at grain boundary in aged AZ91D alloy and there was no discontinuous precipitation up to 2.0 wt.% Sn addition. Moreover, Sn is an inexpensive alloying element that can strengthen the AZ91 alloy by solid solution hardening and precipitation strengthening by the formation of new intermetallic Mg 2 Sn phase, besides it has a high hydrogen voltage that can improve the corrosion resistance [9,11].…”
Section: Introductionmentioning
confidence: 94%
“…The amount of β phase presents in HPDC Mg components can have a significant impact on the material properties and kinetics of dissolution during solution treatment. Some analytical [19,20] and numerical [21,22] models for second phase dissolution kinetics have been developed, but there are few systematic, quantitative studies on the HPDC Mg alloys.…”
Section: Introductionmentioning
confidence: 99%